Design and development of a DTMF based remote home appliance controller using PIC16F873 - Mat Yunus, Nor Asiah; Che Hassan, Che Zaidi; Abdul Rashid, Razali (Jurnal Penyelidikan Sains Sosial, 2025)
This paper discusses the design and implementation of the home appliances controller that uses a ‘Dual-Tone Multi Frequency (DTMF)’ signal from a home telephone. The system incorporates a microcontroller which interfaces with the DTMF decoder IC which transforms the ‘DTMF signal’ to binary and vice versa. This project aims to control the ON and OFF functions of household appliances using Dual-Tone Multi-Frequency (DTMF) signals. This device allows users to control electrical appliances at home simply through a telephone from anywhere. In addition, users can also turn on specific appliances in advance before returning home as a security measure. This device is also equipped with an alarm system that will be activated and automatically notify the owner via a phone call. To activate this device, users only need to make a call to their home and enter a password after twelve ringtones. If the entered password combination is correct, the user will be authorized to control the connected household appliances. The findings of the study indicate the device is capable of controlling the appliances in the house as it can transmit and receive signals from outside the house. This approach offers a user-friendly interface and utilizes existing telecommunication infrastructure, making it a viable alternative for smart home applications. Finally, through an experimental setup, the device was determined to be functioning optimally.